Present bias and corporate tax policies - Kang, Minwook (2021)
Two major forms of corporate tax policies are dividend and profits taxes. Based on conventional corporate theory, these tax policies distort the firm's investment decisions and decrease firm value. However, this paper shows that under hyperbolically discounted preferences, dividend taxation is capable of boosting firm investment in a value-enhancing way. The hyperbolically discounted present value can be interpreted as reflecting irrational myopic preferences or, as we demonstrate, reduced-form implications of corporate agency issues. Both cases result in an underinvestment problem for the firm, but the firm valuation criteria differ. The optimal taxation issue is discussed under a Cobb–Douglas production function setting.